Effect of dopamine D1 receptor antagonist SCH23390 and D1 agonist A77636 on active allothetic place avoidance, a spatial cognition task - Stuchlik, Ales; Vales, Karel (Behavioural brain research, 2006)
Central dopamine neurotransmission is implicated in several physiological and pathophysiological neural processes. In the past years, attention was paid to the role of dopaminergic signaling in the cognitive processes. In the present study, we investigate role of dopamine D1 receptors in spatial cognition using systemic administration of D1-specific agonist A77636 and D1 antagonist SCH23390. Subsequently, animals were tested in a spatial cognition behavioral task, active allothetic place avoidance (AAPA), a task which requires rats to separate spatial stimuli from two continuously dissociated subsets. The D1 agonist A77636 at doses 0.1 and 0.5mg/kg improved the task solution, whilst application of D1 antagonist SCH23390 (0.02 and 0.05 mg/kg) caused an impairment in the AAPA task. These findings support the notion that brain dopaminergic D1 neurotransmitter system modulates neural processes underlying spatial cognition.
Keywords: Analysis of Variance; Animals; vztah mezi dávkou a účinkem léčiva; benzopyrany; Rats, Long-Evans; Avoidance Learning; Space Perception; receptory dopaminu D1; Receptors, Dopamine D1; Exploratory Behavior; Benzopyrans; benzazepiny; Benzazepines; Spatial Behavior; Adamantane; neparametrická statistika; Dose-Response Relationship, Drug; analýza rozptylu; potkani Long-Evans; Male; učení vyhýbat se; krysa rodu Rattus; adamantan; pátrací chování; vnímání prostoru; Statistics, Nonparametric; zvířata; mužské pohlaví; Dopamine Agents; Rats; prostorové chování; dopaminové látky